2007
DOI: 10.1177/160940690700600401
|View full text |Cite
|
Sign up to set email alerts
|

Using Focus Groups to Research Sensitive Issues: Insights from Group Interviews on Nursing in the Northern Ireland “Troubles”

Abstract: In this article the authors discuss the usefulness of focus groups for researching sensitive issues using evidence from a study examining the experiences of nurses providing care in the context of the Northern Ireland Troubles. They conducted three group interviews with nurses during which they asked about the issues the nurses face(d) in providing nursing care amid enduring social division. Through a discursive analysis of within-group interaction, they demonstrate how participants employ a range of interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Jordan et al (2007, p. 2), in their focus group study of nurses in Northern Ireland, found that 'focus groups should be considered most useful for illuminating locally sanctioned ways of talking about sensitive issues.' In the case of research dealing with police, this approach to the sensitivity of issues related to commanding officers or specific local issues can aid understanding of the ways in which Medium City police officers make sense of their local context (Jordan et al, 2007;Krueger, 1993).…”
Section: Participant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jordan et al (2007, p. 2), in their focus group study of nurses in Northern Ireland, found that 'focus groups should be considered most useful for illuminating locally sanctioned ways of talking about sensitive issues.' In the case of research dealing with police, this approach to the sensitivity of issues related to commanding officers or specific local issues can aid understanding of the ways in which Medium City police officers make sense of their local context (Jordan et al, 2007;Krueger, 1993).…”
Section: Participant Selectionmentioning
confidence: 99%
“…Thus, the City Manager and the Human Resources Department were instructed to invite officers who did not have direct oversight of one another. Groups consisted of as few members as possible who were related to each other through a supervisory capacity (Babbie, 2004;Grudens-Schuck, Allen, & Larson, 2004;Hyde, Howlett, Brady, & Drennan, 2005;Jordan et al, 2007;Schutt, 2006;Swayze, 2008).…”
Section: Participant Selectionmentioning
confidence: 99%
“…For mini groups, the number of participants can range from as few as three, four to six, four to as many as twelve, fourteen, depending on the research purposes [16]. Smaller groups are more appropriate if the aim is to explore complex, controversial, emotional topics, sensitive issue or to encourage details accounts [14]. Overall small groups show greater potential [18].…”
Section: Number Of Participantsmentioning
confidence: 99%
“…Altogether there were twelve people involved in the FGD. This is acceptable since as mentioned by [14], and [18], FGD can be conducted in mini groups. Regarding the number of participants in a mini group, as cited in [12], it can go as few as three, depending on the research purposes and it has been successful.…”
Section: Number Of Participantsmentioning
confidence: 99%
“…Lee (1993) suggests that those issues which cause concern about sensitivity in research are those considered private and sacred (sexuality and death), issues which cause stigmatisation and fear (illegal behaviour), and sensitivity in relation to social conflict (political threat). Further to these considerations, I would suggest that sensitive studies are those in which there are potential consequences or implications for researchers and respondents (Jordan et al, 2007). Concern then is not confined to that of the researcher, but more commonly on all who are involved in the research process.…”
Section: Conducting Sensitive Researchmentioning
confidence: 99%